1969
DOI: 10.1063/1.1652900
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Thin Film Switching and Memory Effects in Semiconducting Chalcogenide Glasses

Abstract: Switching phenomena take place in thick bulk samples of semiconducting glass, once a path of devitrified material is established. Potential probe and infrared microradiometer measurements reveal that the switching action takes place in a small region somewhere along this path. Application of voltage pulses can move this region to a different position. Evidence of partial devitrification and melting is also found in thin film switches made from many different glass compositions. Memory switching has also been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…This is driving research on materials systems and architectures for memory devices. [21][22][23][24][25][26] High capacity and low cost write-once-read-many-times ͑WORM͒ memories have advantages over rewritable memories for archival storage applications such as flash memory cards and miniature hard disks. For example, WORM memories require no energy to refresh stored data; an especially important feature for mobile and handheld applications.…”
Section: Introductionmentioning
confidence: 99%
“…This is driving research on materials systems and architectures for memory devices. [21][22][23][24][25][26] High capacity and low cost write-once-read-many-times ͑WORM͒ memories have advantages over rewritable memories for archival storage applications such as flash memory cards and miniature hard disks. For example, WORM memories require no energy to refresh stored data; an especially important feature for mobile and handheld applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several interpretations based on electronic interface states, ionic displacernents, thermal processes, polarization and space charge effects have been suggested. It might be that the current oscillations described here result from thermal devitrification of glass; the transition froin insulating state to conducting state would be related to a1 ocal glass-crystal phase transition due to heating by Joule's effect in thin channels of glass (filamentary conduction [15]). I n conclusion, it was shown that, in convenient experimental conditions, fieldemission microscopy from metallic tips coated with glass can give valuable inforination about the behaviour of glass submitted to very high electric fields.…”
Section: Resultsmentioning
confidence: 94%
“…V-VI chalcogenides are an important compound group which have been widely used as phase-change memory (PRAM) [1][2][3][4][5], thermoelectric [6][7], photoelectronic [8][9][10][11] and chemical sensor [12]. Many phase-change memory and photoelectronic devices are based on chalcogenide thin films.…”
Section: Introductionmentioning
confidence: 99%